Association Between Circulating Lymphocyte Populations and Outcome After Stereotactic Body Radiation Therapy in Patients With Hepatocellular Carcinoma - Zhuang, Yuan; Yuan, Bao-ying; Chen, Gen-wen; Zhao, Xiao-mei; Hu, Yong; Zhu, Wen-chao; Zeng, Zhao-chong; Chen, Yi-xing (Frontiers in Oncology, 2019)
Background and objective: Radiation-induced lymphopenia has a tangible impact on overall survival (OS) in multiple solid tumors. We investigated the association between circulating lymphocyte populations (CLPs) before and after stereotactic body radiation therapy (SBRT) and OS in patients with hepatocellular carcinoma (HCC). Materials and Methods: Seventy-eight HCC patients treated with SBRT between January 2013 and June 2017 were retrospectively analyzed. Baseline and post-treatment total peripheral lymphocyte counts (TPLCs) and values of different CLPs were obtained and analyzed for clinical outcomes. Univariate and multivariate Cox regression analyses were used to explore the independent prognostic factors for patient survival. Results: The one-, two- and three-year OS rates were 94.8%, 75.9%, and 63.3%, respectively. The mean TPLCs before and 10 days after SBRT were 1.4×109/L and 0.7×109/L, respectively. The TPLC recovered to its baseline value one year after SBRT. Multivariate analysis results revealed that variables, including tumor necrosis factor-alpha (TNF-α) level <5.5 ng/mL and post-treatment TPLC <0.45×109/L were independent factors for inferior OS. Further analysis showed that the values of CLPs, including CD3+, CD4+, CD8+, CD19+, and CD16+56+ cells dropped profoundly 10 days after SBRT, among which CD19+ B cell count was mostly depleted and gradually recovered after two months. Univariate analysis showed that both baseline and post-treatment TPLC and CLP (except post-treatment B cell) counts were significantly associated with patient OS (p<0.05 for each). Further stratified analysis performed according to OS at two years demonstrated that the CD16+CD56+ NK cell counts remained significantly elevated in patients with better survival (OS >two years) compared to those in short-term survivors at 10 days, one month, and two months after SBRT (p<0.05 for each). In addition, there were significant differences in TPLC and CD8+ T cell counts in patients with long-term and short-term OS at two months after SBRT (p<0.05). Conclusions: Peripheral lymphopenia after SBRT might be an independent prognostic factor for poorer outcome in HCC patients. Post-treatment lymphocyte subsets, including CD8+ T cell and NK cell counts were also associated with two-year OS rates.